It's not a sprint, it's a marathon: Reviewing governmental R&D support for environmental innovation - Leonie Meißner; Sonja Peterson; Finn Ole Semrau (Kiel Institute for the World Economy (IfW Kiel), 2023)
In a race against excessive global warming, the world must accelerate the development and adoption of environmental innovations (EIs). EIs are crucial in decarbonizing the economy and meeting the netzero targets. In this literature review, we delve into the role of governments in promoting EIs across stages of maturity and the likeliness of such support to reduce emissions and mitigation costs. Various theoretical justifications, such as knowledge externalities, dynamic increasing returns, path dependency and incomplete information, highlight the necessity to promote EI through governmental Research and Development (R&D) support. While emission pricing remains the most cost-efficient climate policy, it fails as a stand-alone instrument to sufficiently encourage EI. Accordingly, the optimal approach is a policy mix complementing emission pricing with governmental R&D support. The theoretical finding is backed by empirical studies on the development and deployment of renewable energies, which also show that investment in R&D can effectively reduce emissions and mitigation costs. By combining theoretical and empirical research, the review concludes by examining two pivotal policy actions aimed at accelerating the take-off of EIs: The US Inflation Reduction Act and the European Green New Deal Industrial Plan. We evaluate their specific aspects and limitations to effectively and efficiently contribute to decarbonization.
Keywords: 330